EXPLORING THE INFLUENCE OF ONLINE DISCUSSION BOARDS ON EQUITY CROWDFUNDING DYNAMICS - Ruchiyat, Endang; Ay, Nyoman Dwika; Budi Raharja , Arif (Yayasan Kreatif Indonesia Emas, 2024)
Equity crowdfunding has become a popular method of funding small and medium enterprises (SMEs) and startups. As internet technology has developed, online discussion forums have also played an increasingly important role in shaping perceptions and investment decisions in the industry. This abstract examines the impact of online discussion forums on the dynamics of equity crowdfunding and how regulations related to both influence the behavior of investors, market players, and technology development. By analyzing relevant literature, it is concluded that online discussion forums play an important role in providing a platform for investors to obtain information, validate investment ideas, and influence overall market sentiment. However, the effectiveness of online discussion forums can be influenced by several factors, including the credibility of the information, the presence of moderators, and interactions between forum members. Meanwhile, regulations relating to equity crowdfunding and online discussion forums can play a complex role in shaping the behavior of investors and market participants. Clear and transparent regulations can increase trust and participation in the industry, while regulations that are too strict or inflexible can stifle growth and innovation. Therefore, it is recommended that governments, regulators and industry players work together to create a regulatory framework that is inclusive, responsive and results-oriented. Public education and awareness about the importance of regulation and judicious use of online discussion forums are also crucial steps in ensuring the survival and health of the industry.